Site characteristics determine the duration of structure liming effects on clay soil - Blomquist, Jens Erik; Englund, Jan-Eric; Berglund, Kerstin (Agricultural and Food Science, 2022)
Adding carbonated or non-carbonated lime to clay soils can lead to changes in aggregate stability. In Sweden, ‘structure liming’ with a mixed product (normally 80–85% calcium carbonate and 15–20% calcium hydroxide) is subsidised through environmental schemes to increase aggregate stability, thereby mitigating losses of particulate phosphorus (PP). This study assessed the effects of structure liming on aggregate stability in eight clay soils in southern Sweden, using turbidity as a proxy for aggregate stability. Turbidity in leachate from simulated rain events performed on aggregates (2–5 mm) in the laboratory was measured one and six years after application of four treatments 0, 4, 8 and 16 t ha-1 of a mixed structure liming product. The effect on turbidity was analysed for all application rates, but also as the contrast between the unlimed control and the mean of the limed treatments, to identify the general effect. A significant effect of structure liming on turbidity was found after one year. The effect decreased over time, but was still detectable after six years. However, there was a significant interaction between trial and treatment, indicating different reactions on different soils and suggesting that not all clay soils are suitable for structure liming if the desired objective is to lower the risk of PP losses. Clay content, initial pH and mineralogy may explain the different responses to structure liming. These findings show a need for a site-specific structure liming strategy. As a tentative recommendation, soils with a minimum clay content of approximately 25–30% and pH <7 should be preferred for structure liming.